Effects of the Sharing Economy on Sequential Innovation Products - Zhenfeng Liu; Jian Feng; Jinfeng Wang (Complexity)
The emergence of the sharing economy has affected consumers and traditional manufacturers. We focus on product sharing and analyze its impacts on the manufacturer that offers sequential innovation products. We develop a two-period model in which a monopoly manufacturer sells an old product and introduces a new product in each period; in the same period, an owner who bought a product for self-use from the manufacturer in the previous period may rent the product out because of the low self-use value in this period. Our analysis reveals that the sharing market increases or decreases the manufacturer’s profit, and this is mainly determined by the moral hazard cost and the salvage value of sharing products. Furthermore, the sharing market has an insignificant effect on the upgrading of products, but there is a bumping-down effect on old products’ sales. Finally, the effect of the sharing market on the revenue of the owner and the sharing platform mostly depends on the risk of moral hazard, and it also affects the manufacturer’s product rollover strategy.